Design and analysis of tissue engineering scaffolds that mimic soft tissue mechanical anisotropy - Courtney, T.; Sacks, M.S.; Stankus, J.; Guan, J.; Wagner, W.R.
Tissue engineered constructs must exhibit tissue-like functional properties, including mechanical behavior comparable to the native tissues they are intended to replace. Moreover, the ability to reversibly undergo large strains can help to promote and guide tissue growth. Electrospun poly (ester urethane)ureas (ES-PEUU)are elastomeric and allow for the control of fiber diameter, porosity, and degradation rate. ES-PEUU scaffolds can be fabricated to have a well-aligned fiber network, which is important for applications involving mechanically anisotropic soft tissues. We have developed ES-PEUU scaffolds under variable speed conditions and modeled the effects of fiber orientation on the macro-mechanical properties of the scaffold. To illustrate the ability to simulate native tissue mechanical behavior, we demonstrated that the high velocity spun scaffolds exhibited highly anisotropic mechanical properties closely resembling the native pulmonary heart valve leaflet. Moreover, use of the present fiber-level structural constitutive model allows for the determination of electrospinning conditions to tailor ES-PEUU scaffolds for specific soft tissue applications. The results of this study will help to provide the basis for rationally designed mechanically anisotropic soft tissue engineered implants. © 2006 Elsevier Ltd. All rights reserved.
Keywords: ANISOTROPY; BIOMECHANICS; ELASTOMERS; FIBER REINFORCED MATERIALS; MECHANICAL PROPERTIES; POLYESTERS; POROSITY; PULMONARY DISEASES; SCAFFOLDS; STRAIN; UREA